সিলেটি নাগরী : ফকিরি ধারার ফসল - সাদিক, মোহাম্মদ, ১৯৫৫-; Asiatic Society of Bangladesh (ঢাকা : বাংলাদেশ এশিয়াটিক সোসাইটি, 2008)
Study on Sylheti script, a dialect of Bengali language of Sylhet District, Bangladesh.
Title in Sylheti script also.
গ্রন্থপঞ্জিগত নির্দেশিকা (পৃষ্ঠা ২১৯-২৩৯) ও নির্ঘণ্ট অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali; includes passages in English and Sylheti dialect (Bengali).
Keywords: Bengali language -- Dialects -- Bangladesh -- Sylhet District; Sylheti dialect; Sylhet District (Bangladesh) -- Languages